2014
DOI: 10.7603/s40681-014-0009-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to idiopathic membranous nephropathy in high-prevalence Area, Taiwan

Abstract: Idiopathic membranous nephropathy (MN) is one common cause of idiopathic nephrotic syndrome in adults; 25% of MN patients proceed to end-stage renal disease. In adults, membranous nephropathy is a lead cause of nephrotic syndrome, with about 75% of the cases idiopathic. Secondary causes include autoimmune disease, infection, drugs and malignancy. Three hypotheses about pathogenesis have surfaced: preformed immune complex, in situ immune complex formation, and auto-antibody against podocyte membrane antigen. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The expression of mRNAs encoding TLR4 was increased in IgA nephropathy, which presented with immune deposits of IgA within glomeruli (Donadio et al., ). Subsequently, TLR4 was claimed to be associated with membranous nephropathy, which is considered a non‐inflammatory organ‐specific autoimmune disease (Chen et al., ). The current study emphasized the effect of TLR4 on membranous nephropathy progression by affecting podocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of mRNAs encoding TLR4 was increased in IgA nephropathy, which presented with immune deposits of IgA within glomeruli (Donadio et al., ). Subsequently, TLR4 was claimed to be associated with membranous nephropathy, which is considered a non‐inflammatory organ‐specific autoimmune disease (Chen et al., ). The current study emphasized the effect of TLR4 on membranous nephropathy progression by affecting podocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports of a genetic susceptibility to idiopathic membranous nephropathy. This type of study was conducted in a high-prevalence area in Taiwan [97]. In these studies, the association of the IL-6, NPHS1 (nephrin), TLR-4, TLR-9, STAT4 (signal transducer and activator of transcription) and MYH (mutY DNA glycosylase), genes with susceptibility to primary membranous nephropathy in Taiwan was established.…”
Section: Membranous Nephropathy (Mn)mentioning
confidence: 99%
“…In recent years, numerous studies have indicated that certain genetic polymorphisms associated with susceptibility to this disease. [ 5 , 6 ] And this discovery has opened a new horizon in the therapy of iMN.…”
Section: Introductionmentioning
confidence: 99%